AGRICULTURAL PESTICIDE USE IN THE UPPER CITARUM RIVER BASIN: BASIC DATA FOR MODEL-BASED RISK MANAGEMENT - Utami, Rosetyati R.; Geerling, Gertjan W.; Salami, Indah R. S.; Notodarmojo, Suprihanto; Ragas, Ad M.J. (Journal of Environmental Science and Sustainable Development, 2020)
Since the middle of the 20th century, pesticide use has been a primary foundation of global agricultural development. However, the massive usage of pesticides can have detrimental impacts on human health and the environment, particularly in the aquatic ecosystem. This study determined the use of pesticides in the agricultural area of the Upper Citarum River Basin (UCRB); a crucial water resource on Java Island. A survey of 174 farmers was conducted in eight districts along the basin by using the random walk and quota sampling method. The questionnaire was designed to acquire data about the amount and types of pesticides used by farmers. Pre-survey was conducted to evaluate the feasibility of the questionnaire draft. The respondents’ answers were inputted into an equation to estimate the pesticide use per year. The survey results showed that 31 different pesticides were used for 21 types of crops. Profenofos and Mancozeb were the two most used pesticides, among all. The highest annual average used per hectare was reported for Chlorothalonil on tomato (32.2 kg/ha/year), followed by Mancozeb on corn (28.6 kg/ha/year), and Chlorpyrifos on chili (26.1 kg/ha/year). Overall, the pesticide use estimation in the study area is relatively high, with an annual average of 24.6 kg/ha/year. A comparison between prescribed and actual use on rice (representing more than 64% of the total surveyed area) showed that most pesticides are used in line with the prescriptions, but about a quarter is used in larger amounts than recommended. This comparison also revealed that some farmers use pesticides for rice that are not recommended for rice farming. In conclusion, the data presented in this study can be used to estimate pesticide emissions for environmental risk assessment and to support water quality monitoring, especially since public accessibility of pesticide information is commonly limited in Indonesia and other low- and middle-income countries.